A heterogeneous decision criteria system evaluating sustainable infrastructure development: From the lens of multidisciplinary stakeholder engagement. (7th November 2021) - Xue, Bin; Liu, Bingsheng; Liang, Tao; Zhao, Dong; Wang, Tao; Chen, Xingbin
Abstract: The evaluation of urban infrastructure development is a decision‐making process with multidisciplinary stakeholder engagement assessing sustainability metrics in different dimensions. However, there are uncertainties in such an evaluation caused by the heterogeneity between different stakeholders' preferences and the difficulty in differentiating sustainability decision criteria (DC). This study aims to formalize a multidisciplinary DC system to evaluate sustainable infrastructure development, which represents the preferences to DC metrics heterogeneously weighted by stakeholders. An empirical survey was conducted to collect the stakeholders' preferences to 50 sustainability DC metrics in which 91 infrastructure professionals from six disciplines (i.e., owner, architect, engineer, contractor, supplier, and consultant) were invited to participate. As a result, this study identified one common and six disciplinary DC sets and defined 20 DC factors with weights information structuring the multidisciplinary decision‐making process, which indicates the multidisciplinary DC system is formal to be leveraged on assessing the sustainability performance of infrastructure development. In addition, the proposed multidisciplinary DC system is comprehensive in reducing uncertainties through determining the weights of DC metrics across various disciplines. Theoretically, the multidisciplinary DC system advances the knowledge of sustainability measurement by not only integrating the planet–people–prosperity framework and the product–organization–process framework but mitigating evaluation uncertainty through representing stakeholders' heterogeneity. For practical significance, such a multidisciplinary DC system will serve as a precursor for managers and policymakers in decision‐making processes to enhance sustainability performances of infrastructure development.